Biology of Tiger Moth (Atteva Sciodoxa Meyrick) Infesting Tongkat Ali (Eurycoma Longifolia Jack) and its Control by Beauveria Bassiana - Bajwa, Ghulam Ali (2009)
Eurycoma longifolia is a widely used medicinal plant in South East Asia. Atteva sciodoxa, the small golden brown moth, became serious pest with the onset of E. longifolia plantations. The widespread medicinal use of E. longifolia and deleterious effects of chemical insecticides led to search non-chemical control of A. sciodoxa. The research was undertaken to study some biological aspects of A. sciodoxa and to assess potential of entomopathogenic fungus Beauveria bassiana to control A. sciodoxa. A. sciodoxa feeds gregariously by building communal webs on the terminal shoots. The infestation ranged between 65.0±2.03% and 92.6±1.13%. A. sciodoxa completed its five larval instars in 20.7±0.2 days while lifecycle duration in 46.3±0.49 days. The population rate of increase ranged between 0.33 and 1.39 female off springs per female. The net reproductive rate, mean generation time and population doubling time were 42.03 female offsprings per female, 11.41 days and 2.12 days respectively. The highest apparent, real and indispensable mortality were in first instar larvae. The lower threshold temperature was between 9.2°C and 14.7°C while the thermal constant ranged from 126.4 to 79.3 degree-days for different metamorphic stages. The mean food ingestibility, efficiency of conversion of ingested food, efficiency of conversion of digested food and approximate digestibility were 75.2±0.32%, 67.8±0.74%, 37.0±1.21% and 63.10.73%, respectively. The mean food consumption index was 0.23 mg dry leaf per mg larval body weight per day while relative growth rate was 0.08 mg body larval weight gain per mg larval body weight per day. Seven B. bassiana isolates obtained from different sources were screened for pathogenicity. All the isolates were found to be pathogenic. The degree of pathogenicity varied significantly among the isolates. The earliest mortality was recorded on day three after inoculation in five isolates. The most virulent isolate was Bba-Pp with 100% mortality and median effective time of 3.6 days. The least infective isolate was Bba-Sl3 with 24.9±2.10% mortality and the median effective time of 15.3 days. The median effective concentration was 9.89x105 and 3.85x106 conidia ml-1 for Bba-Pp and FS-11, respectively. Mycosis time differed significantly among isolates. Isolate Bba-Pp appeared earliest on cadavers in 24 h. The conidial production ranged between 1.2±0.84x106 and 1.5±3.30x107 conidia per mg cadaver in the seven tested isolates. Isolate Bba-Pp decreased food consumption by 72.5% at concentration of 1x107 conidia ml-1 as compared to the control. The age specific dose mortality response revealed high infectivity of B. bassiana Bba-Pp in all metamorphic stages of A. sciodoxa. The highest egg infectivity was 22.6±1.60% when 24 h-old eggs were inoculated at 1x108 conidia ml-1 while the highest delayed first instar larval mortality was 85.6±2.30% when eggs were inoculated at 24 h before hatching at 1x108 conidia ml-1. The third instar larva was most susceptible while the fifth instar larva was the least. The median effective concentration ranged between 9.87x105 and 21.3x105 conidia ml-1 for third to fifth instar larvae while the median effective time ranged from 3.3 to 8.2 days for three tested larval instars at different concentrations. There was a significant temperature effect on B. bassiana Bba-Pp infectivity with optimum range between 27°C and 30°C. Infectivity, mycosis and sporulation were strongly affected when larva, leaf, or both, were inoculated by B. bassiana Bba-Pp. Larval mortality ranged between 38.1±3.21% and 94.6±2.40% in three exposure methods. Larval mortality of 54.1±1.74% was recorded due to secondary acquisition of conidia from spray residues on the foliage of E. longifolia. The shortest mean mycosis time was 20.2±0.37 h when both larvae and leaves were inoculated and cadavers incubated at 30°C while the longest was 28.0±0.45 h when only leaves were inoculated and cadavers incubated at 21°C. The highest conidial production was 150.9±0.01x105 conidia per mg cadaver when both larvae and leaves were inoculated at a concentration of 1x108 conidia ml-1 and cadavers incubated at 27ºC. The lowest conidial production was 46.6±0.02x105 conidia per mg cadaver when only leaves were inoculated at a concentration of 1x107 conidia ml-1 and cadavers incubated at 33°C. The highest conidial germination and the longest germ tube length was 99.2±0.37% and 45.6±0.84 μm at 27ºC, respectively. The optimum temperature for mycosis, sporulation, conidial germination and germ tube growth rate was between 27ºC and 30ºC. B. bassiana Bba-Pp was transmitted horizontally from exposed to unexposed larvae, via infective cadavers and contaminated faeces. The highest net transmitted mortality was 87.5±1.17% when exposed larvae were inoculated at 1x108 conidia ml-1 and mixed with same number of unexposed larvae. There was significant effect of concentration and ratio on net transmitted mortality. The highest transmitted mortality via infective cadaver was 92.1±1.31% at a density of 0.12 cadaver cm-2. Viable B. bassiana Bba-Pp was isolated from faeces when larvae were inoculated by different exposure methods and at different concentrations. The highest number of B. bassiana Bba-Pp colonies isolated was 15.5±0.12x103 per mg faeces isolated on day one following inoculation of both larvae and leaves at concentration of 1x108 conidia ml-1. The number of B. bassiana colonies was influenced by exposure method, concentration and the time following inoculation. Larval mortality of 42.2±1.36% was caused when larvae exposed to faeces with 15.5±0.12x103 B. bassiana colonies per mg. The findings biological studies indicated that A. sciodoxa has characteristics of a serious pest. The results also showed high infectivity, residual effect, horizontal transmission and recycling capacity of B. bassiana in A. sciodoxa. Based on these findings it is concluded that B. bassiana Bba-Pp has potential to control A. sciodoxa.